2009
DOI: 10.1093/ndt/gfp383
|View full text |Cite
|
Sign up to set email alerts
|

The association of depressive symptoms with survival in a Dutch cohort of patients with end-stage renal disease

Abstract: Patients with ESRD treated with dialysis show a high level of depressive symptoms that is independently associated with poor survival. Future research should address appropriate therapeutic regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 27 publications
1
53
0
Order By: Relevance
“…172 Symptoms of depression are more frequent with reduction in kidney function and relate to poor outcome and mortality. [173][174][175] Cytokines are thought to be important mediators of brain immune connection and may play an important role in the pathogenesis of depression because of their effect on neurotransmitters and neurohormones. 173,176 In dialysis patients, symptoms of depression are associated with increased IL-6 levels, 177,178 and 8 weeks of fluoxetine treatment resulted in decreased serum IL-1b levels.…”
Section: Comorbidities and Lifestyle Comorbiditiesmentioning
confidence: 99%
“…172 Symptoms of depression are more frequent with reduction in kidney function and relate to poor outcome and mortality. [173][174][175] Cytokines are thought to be important mediators of brain immune connection and may play an important role in the pathogenesis of depression because of their effect on neurotransmitters and neurohormones. 173,176 In dialysis patients, symptoms of depression are associated with increased IL-6 levels, 177,178 and 8 weeks of fluoxetine treatment resulted in decreased serum IL-1b levels.…”
Section: Comorbidities and Lifestyle Comorbiditiesmentioning
confidence: 99%
“…Depression is a common problem in ESRD patients 31 and related to high mortality. 32,33 In peritoneal dialysis (PD) patients, depression was strongly related to inflammation, malnutrition, and multiple cardiovascular risk factors, suggesting that depression is an integral part of the MIA syndrome. 34 Indeed the state of depression associates with activation of proinflammatory cytokines, and patients on maintenance HD with symptoms of depression were more likely to have high levels of serum IL-6, higher prevalence of comorbidities, higher serum total cholesterol, and lower s-albumin levels.…”
Section: General Lifestyle Modifications That May Have Anti-inflammatmentioning
confidence: 99%
“…Furthermore, in addition to having greater mortality risk, depressed patients report poorer quality of life (2). Recent studies have also demonstrated an association between depressive affect, manifested by depressive symptoms, with higher mortality among patients with ESRD (3)(4)(5)(6)(7). Depressive symptoms and associated outcomes have been assessed by self-report using two questions within the Medical Outcomes Study Short Form 36 (SF-36) (4,5).…”
Section: Introductionmentioning
confidence: 99%